Investigating the Dynamic Behavior of Gabbro Specimens With Echelon Joints - Lei Xue; Shihao Yuan; Kangqi Liu; Longfei Li; Kun Huang; Zhuan Li (Energy Science & Engineering)
ABSTRACT To reveal the influence of dynamic load on the dynamic damage behavior of jointed rock masses, split Hopkinson pressure bar (SHPB) system was employed to test platy gabbro samples with joint angles of 15°, 30°, 45°, 65°, and 75° at an impact pressure of 0.1 MPa. It was found that the joint angle has a significant effect on the dynamic characteristics and fracture behaviors of the echelon gabbro samples. Samples with a joint angle of 15° required the least amount of fracture energy and was most prone to failure, while samples with a joint angle of 30° required the most amount of fracture energy and was difficult to fracture. Moreover, the joint angle controlled the damage mode of the specimen. Specimens with 15° and 30° joint angles corresponded to crack coalescence type I, where the main crack was a shear crack and was nearly straight. Specimens with 45° and 60° joint angles corresponded to crack coalescence type II, where the main crack was a shear crack, and a small number of tensile secondary cracks developed. Specimens with a joint angle of 75° corresponded to crack coalescence type III, where the main crack was a shear crack and a large number of tensile cracks developed.